Lead-free solders - Prabhu, Narayan (ASTM International, 2011)
"Eleven peer-reviewed papers address the environmental and health concerns related to the exposure to lead during soldering and the success and failures of lead-free solders. Topics cover: Factors affecting the wetting behavior of solders and evolution of interfacial microstructure ; Pb-free high temperature solders for power semiconductor devices ; Effect of surface roughness on wetting behavior and evolution of microstructure of two lead free solders on copper substrates ; Fatigue life of SnBi Finished thin-small-outline-package (TSOP) parts under thermal cycling ; Microstructural aspects of the ductile-to-brittle transition ; Loading mixity on the interfacial failure mode in lead-free solder joint ; Solder joint strengths of BGA (Ball Grid Array) lead-free to that of eutectic lead (Sn-Pb) solder joint strengths. ; Effect of the morphology of Cu6Sn5 intermetallic compound on tensile properties of bulk solder and solder joint ; Tensile properties of Sn-10Sb-5Cu high temperature lead free solder ; Empirical modeling and rheological characterization of solder pastes used in electronic assemblies. STP 1530 is a valuable resource for students, researchers, and material scientists in the electronic industry."--Publisher's website.
"Sponsored by ASTM Committee D02 on Petroleum Products and Lubricants"--Page [iii].
Keywords: Lead-free electronics manufacturing processes.; Solder and soldering -- Materials.; elektronické knihy; electronic books